Agricultural Livelihood Types and Type-Specific Drivers of Crop Production Diversification: Evidence from Aral Sea Basin Region - Akramkhanov, Akmal; Akbarov, Adkham; Umarova, Shakhzoda; Le, Quang Bao (MDPI, 2023)
Understanding the factors driving the farmers’ decisions to diversify their crop production is important for management strategies and policies promoting climate-smart agricultural development. Options for diversification and its associated drivers might be shaped by livelihood context, and it remains as a general gap in knowledge. This study aimed to reveal the driving factors behind households’ decisions to diversify their crops in different livelihood contexts. This information could be useful to inform stakeholders on a set of context-fitted options for improving natural resources and rural livelihood resilience to climatic variability and risks. This study applied the Sustainable Livelihood Framework (SLF) to guide surveys and multivariate analyses that identified agricultural livelihood context types at the village level, and also evaluated both the common and type-specific drivers encouraging households to diversify their agricultural production in two rural villages in the Aral Sea region. This study objectively identified three distinct agricultural livelihood types and the main factors differentiating these types from each other. When the total sampled population was analyzed, the results indicated that the agricultural experience of the household heads, levels of education, sources of income, number of cattle and land endowments, and proximity to markets were common and significant drivers in diversifying these households’ crop production. Analyzing the decisions behind diversifying crop production for each agricultural livelihood type revealed type-specific drivers of diversification. The findings suggested that considering both common and type-specific drivers of diversification would allow better understanding of household decisions and provide more insights to develop effective policies promoting climate-smart agriculture through diversification, rather than continuing to use the current “uniform blanket” approach.